A Glyphosate Pulse to Brackish Long-Term Microcosms Has a Greater Impact on the Microbial Diversity and Abundance of Planktonic Than of Biofilm Assemblages - Janßen, René; Skeff, Wael; Werner, Johannes; Wirth, Marisa A.; Kreikemeyer, Bernd; Schulz-Bull, Detlef; Labrenz, Matthias (Frontiers in Marine Science, 2019)
The widespread herbicide glyphosate has been detected in aquatic coastal zones of the southern Baltic Sea. We monitored community dynamics in glyphosate-impacted chemostats for 20 weeks to evaluate the potential impact of the herbicide on free-living and biofilm-associated bacterial community assemblages in a brackish ecosystem. A HPLC-MS/MS method was developed to measure glyphosate, aminomethylphosphonic acid and sarcosine concentrations within a brackish matrix. These concentrations were analyzed weekly, together with prokaryotic succession, determined by total cell counts and next generation 16S rRNA (gene) amplicon sequencing. Shotgun metagenomics provided insights into the glyphosate degradation potential of the microbial communities. Temporal increases in total cell counts, bacterial diversity and the abundances of distinct bacterial operational taxonomic units were identified in the water column. Biofilm communities proved to be less affected than pelagic ones, but their responses were of longer duration. The increase of gox and thiO gene and the phn operon gene abundance indicated glyphosate degradation by first the aminomethylphosphonic acid pathway and possible subsequently by cleaving the C-P bond. However, although glyphosate concentrations were reduced by 99 %, 1 µM of the herbicide remained until the end of the experiment. Thus, when present at low concentrations, glyphosate may evade bacterial degradation and persist in Baltic Sea waters.